2016
DOI: 10.5206/cie-eci.v45i2.9288
|View full text |Cite
|
Sign up to set email alerts
|

The Post-Sojourn in Study Abroad Research—Another Frontier

Abstract: The conference brought together researchers and practitioners from across the world for presentations and discussions on various facets of residence and study abroad (SA) for second languages (L2). While concerned with the broadly defined topic of culture in the SA context, the conference's call for papers emphasized five specific sub-themes: participants' / stakeholders' culture; cultural and intercultural learning (in relation to language acquisition); the post-sojourn effect of cultural learning; the cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…(The post-study abroad tests were conducted on return and 15 months post-sojourn whilst the participants were still students.) More pertinent, however, to the present study and the research direction identified by Plews (2016) is recent research on the wider consequences poststudy abroad. Studying in Japan was found to present a "critical incident" in life trajectories (Campbell, 2016), with post-sojourners remaining connected with the country in different ways.…”
Section: The Post-study Abroad Contextmentioning
confidence: 91%
See 1 more Smart Citation
“…(The post-study abroad tests were conducted on return and 15 months post-sojourn whilst the participants were still students.) More pertinent, however, to the present study and the research direction identified by Plews (2016) is recent research on the wider consequences poststudy abroad. Studying in Japan was found to present a "critical incident" in life trajectories (Campbell, 2016), with post-sojourners remaining connected with the country in different ways.…”
Section: The Post-study Abroad Contextmentioning
confidence: 91%
“…Citing Kinginger's (2004) Alice Doesn't Live Here Anymore, Plews (2016, p. 3) commented: "…we are left asking what must also have gone on at home, whether there was no going back to her former self…". The post-sojourn in study abroad research has been described as "Another Frontier" with the sustaining of language gains, attrition, and endurability of identity positions highlighted as ripe for further exploration (Plews, 2016). Coleman (2013, p. 27) asked: "Do we not need more studies which address both lifewide and lifelong outcomes?"…”
Section: Introductionmentioning
confidence: 99%
“…The project took shape in discussions with my colleagues Kevin McManus and Robert Schrauf as we contemplated responding to a call for research proposals on post-secondary international education from the United States Department of Education. Prior research in applied linguistics had neglected to study the aftermath of overseas language programs, to the point where Plews had identified post-study abroad as a new ‘frontier’ (2016). Our review of the literature had revealed a number of larger-scale studies of non-linguistic outcomes from academic focus (Hadis, 2005) and preparedness for international careers (Franklin, 2010) to global engagement (Paige, Fry, Stallman, Josic, & Jon, 2009), but painfully few studies with an explicit focus on language learning.…”
Section: How I Learned To Love the Surveymentioning
confidence: 99%
“…Although longitudinal studies can be procedurally and logistically difficult, Coleman (2013) pointed out that humans are the longest lived of primates, and that the significance of dramatic life events can hardly be well understood in short-term studies with posttests delayed by a few weeks or months. Plews (2016) went so far as to name the postsojourn period "a new frontier" in which researchers should investigate such issues as the maintenance of language ability, the mobilization of cultural insights, or the durability and adaptation of identity positions over time and in various contexts. Tullock (2018) called for a longitudinal perspective and an emphasis on lifelong identity negotiation; only such approaches can show how sojourns abroad serve as "launching points for long-term transnational identities" (p. 271).…”
mentioning
confidence: 99%